Propitious Escalation in Photocurrent Response from MnZnO3 Thin Films Using Methanol as Sacrificial Agent - Mansoor, Muhammad Adil; Lim, Su Pei; Yusof, Farazila; Ming, Huang Nay (Springer, 2019)
Abstract: The thin film of MnZnO3 was prepared from Mn-Zn complex [Mn2Zn2(TFA)8(THF)4]n(1) (where TFA = trifluroactetato and THF = tetrahydrofuran) via aerosol-assisted chemical vapour deposition. The stoichiometry and oxidation of individual elements of the films were determined by x-ray photoelectron spectroscopy. The field emission gun-scanning electron microscopic images confirmed that the film deposited at 500°C show an agglomerated flower-like structure. The photoelectrocatalytic performance of as-deposited MnZnO3 was evaluated for methanol oxidation using 1Sun illumination (100 mW cm−2). The MnZnO3 photoelectrode showed a photocurrent density of 2.5 mA cm−2 in the presence of 0.6 M methanol, which is three times of that in the absence of methanol. Furthermore, the chronoamperometric results revealed that the films are highly stable and resistive towards photo-corrosion under alkaline media. Impedance studies further elucidated the addition of minute quantity of methanol accelerates the charge transfer by its rapid photoxidation. Graphical Abstract: [Figure not available: see fulltext.] © 2019, The Minerals, Metals & Materials Society.